Bone Turnover Markers in Response to Ultrasound-Guided Microwave Ablation for Primary Hyperparathyroidism - Ni, Wenjing; Yuan, Yue; Chu, Xiaoqiu; Chen, Guofang; Han, Xue; Li, Jie; Wu, Xinping; Wang, Jianhua; Liu, Chao; Xu, Shuhang (Frontiers in Endocrinology, 2021)
Objective: To assess the efficacy and safety of ultrasound-guided microwave ablation (MWA) in the treatment of primary hyperparathyroidism (PHPT), and to investigate whether MWA can improve the bone turnover and renal function. Methods: A total of 20 consecutive PHPT patients with 21 parathyroid lesions treated with MWA in our center from May 2019 to March 2021 were recruited in this study. Serum parathyroid hormone (PTH), calcium and phosphorus levels before MWA and at 20 minutes, 4 hours, 1 day, 3 months, 6 months and 12 months after MWA were measured. Bone turnover biomarkers, renal function and lesion volume with volume reduction rate (VRR) before MWA and at the last follow-up were compared. Any complication related with MWA was evaluated. The technical and clinical success rates of MWA in the treatment of PHPT were calculated. Clinical success was defined as normal serum PTH and calcium without PHPT-associated manifestations at more than 6 months after ablation. Technical success was defined as complete ablation indicated by immediate postoperative contrast-enhanced ultrasound. Results: The serum PTH, calcium and phosphorus levels at their respective follow-up time points dropped significantly after MWA (P <0.05). The volume of parathyroid lesions at the final examination was significantly reduced, compared with pre-ablation volume (P <0.001), with a median VRR reaching 89%. The technical and clinical success rates were 100% and 63.6%, respectively. Substantial changes of bone turnover biomarkers were observed before and after MWA (P <0.05), but the differences in renal function were not statistically significant. No major complications were reported in all cases. Pre-MWA serum PTH, lesion volume, maximum diameter of lesion and ablation time were significantly different between patients with successful and failed MWA. Conclusions: PHPT can be effectively and safely treated by ultrasound-guided MWA, as proven by drop in serum PTH and shrinkage in the volume of parathyroid adenomas. Besides, MWA can impede bone remodeling to suppress hyperparathyroidism in the condition of PHPT.